Food Super Store Shopping Environment and Consumer Impulsive Buying Behavior - Muqaddas, Muhammad Fahid; Azfer, Syed Ali (Táplálkozásmarketing, 2017)
This study examines the impact of food super store shopping on impulsive buying behavior. The results highlight that discounted price, advertisement &promotion, visual merchandising and emotional attachment, have impact on consumer impulsive buying behavior but special occasions and companion’s influence donot impact consumer impulsive buying behavior. The study is based on a sample of food super store buyers from Rawalpindi and Islamabad. The exploration is useful for marketers to understand impulsive consumers and their choices. Food super stores are one of the growing businesses in Pakistan; therefore, this study will guide the marketers to understand this market segment effectively. The study also discovers the association between food super store shopping environment and types of consumer impulsive buying behavior which are cognitive impulsive buying and affective impulsive buying. JEL codes: M31, M37, M39